Multi-user navigation: a 3D mobile device interactive support - Mantoro, Teddy; Abubakar, Adamu; Ayu, Media Anugerah (2011)
Multi-User navigation within an environment with the aid of 3D mobile support provides end users with additional mobility thought and improves mobility services’ efficiency. A necessary approach of using mobile device for navigation aid is to display only a section of the view-front and to let users control the portion shown by conceptually moving on the orientation. There is a need for multiple users to be able to interact with themselves when they are within an environment and navigating with the aid of 3D mobile devices support, in order to meet-up with an appointment or to be aware of the locations of each other. Unfortunately, the predominant 3D mobile navigation system does not provide multi-user interactive services. Users cannot be aware of other users navigating within same environment using the same system on their mobile devices at the same time. This paper presents multi-user 3D mobile navigation system for providing multiple user awareness. The analysis of the results provides a unique visualization of multiple users using mobile devices to help them navigate to a target location by being aware of their whereabouts.